149k views
1 vote
Which expression is equivalent to 4f/3÷1/4f​

User Luc C
by
6.2k points

2 Answers

3 votes

Answer:


\large\boxed{(4f)/(3)/(1)/(4f)=(16f^2)/(3)}

Explanation:


(4f)/(3)/(1)/(4f)=(4f)/(3)\cdot(4f)/(1)=((4f)(4f))/((3)(1))=(16f^2)/(3)

User Gonzalo Matheu
by
5.4k points
3 votes

Answer:


(16f^(2))/(3) is the solution.

Explanation:

The given expression is in the form of


(4f)/(3)/(1)/(4f)

To solve this expression we will convert the sign of division into multiplication.


(4f)/(3)* (4f)/(1)

Now we will multiply the terms of numerator and denominator.


=((4f)(4f))/(3* 1)


=(16f^(2))/(3)

So the simplified form of the given expression is
(16f^(2))/(3)

User Deep Ghodasara
by
5.8k points